El liderazgo efectivo en los centros concertados de naturaleza cooperativa: Percepciones de sus docentes - López Belmonte, Jesús; Fuentes Cabrera, Arturo; Moreno Guerrero, Antonio José (Universidad de Costa Rica, 2018)
Leadership is considered an attribute of people who possess certain skills to achieve the dynamism of the collective of an organization and change the attitude of workers in order to increase the predisposition and performance of people. The purpose of this research is to know the perceptions of teachers about the concept of leadership in a teaching cooperative. The study developed is descriptive and correlational, through an analysis from a quantitative approach for the entire population of teachers who make up the teaching cooperatives of the Autonomous City of Ceuta, in Spain. The data collection was carried out by means of a questionnaire, to which the construct validity and reliability by means of Cronbach's Alpha have been applied. The descriptive analysis describes each of the analyzed variables, while the correlative analysis has been carried out through the Chi-square test to know if there was a relationship between the variables. To know the strength of the relationship, the Kendall Tau-b test was applied. The results show that there is no direct relationship between the variables gender and leadership, and age and leadership. The conclusions show that the leader in education must influence all the members of the educational community, in order to improve the quality of the teaching-learning processes and foster a good climate of social relations